The need for a behavioural science focus in research on mental health and mental disorders. Issue 1 (January 2014) - Wittchen, Hans‐Ulrich; Knappe, Susanne; Andersson, Gerhard; Araya, Ricardo; Banos Rivera, Rosa M.; Barkham, Michael; Bech, Per; Beckers, Tom; Berger, Thomas; Berking, Matthias; Berrocal, Carmen; Botella, Christina; et al.
Abstract Psychology as a science offers an enormous diversity of theories, principles, and methodological approaches to understand mental health, abnormal functions and behaviours and mental disorders. A selected overview of the scope, current topics as well as strength and gaps in Psychological Science may help to depict the advances needed to inform future research agendas specifically on mental health and mental disorders. From an integrative psychological perspective, most maladaptive health behaviours and mental disorders can be conceptualized as the result of developmental dysfunctions of psychological functions and processes as well as neurobiological and genetic processes that interact with the environment. The paper presents and discusses an integrative translational model, linking basic and experimental research with clinical research as well as population‐based prospective‐longitudinal studies. This model provides a conceptual framework to identify how individual vulnerabilities interact with environment over time, and promote critical behaviours that might act as proximal risk factors for ill‐health and mental disorders. Within the models framework, such improved knowledge is also expected to better delineate targeted preventive and therapeutic interventions that prevent further escalation in early stages before the full disorder and further complications thereof develop. In contrast to conventional "personalized medicine" that typically targets individual (genetic) variation of patients who already have developed a disease to improve medical treatment, the proposed framework model, linked to a concerted funding programme of the "Science of Behaviour Change", carries the promise of improved diagnosis, treatment and prevention of health‐risk behaviour constellations as well as mental disorders. Copyright © 2013 John Wiley & Sons, Ltd.